2016
DOI: 10.1007/s10143-016-0788-6
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of the blood vessels of the spinal cord: a comprehensive review

Abstract: There is growing evidence that the nervous system influences spinal cord vasculature. However, most descriptions of the spinal cord have paid little attention to this important aspect. We reviewed the literature on the innervation of spinal cord vessels with an emphasis on findings that may be applicable to human medicine. Multiple neurotransmitters and competing theories have been implicated in the neural regulation of spinal cord blood vessels. Identifying valid mechanisms of pathogenesis could be beneficial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…These form a coronary artery ring at the level of the conus medullaris, which then branches from the artery ring into the conus medullaris. In addition, the thick nerve root medullary artery (Adamkiewicz artery) from the intercostal or lumbar artery from T9 to T12 and the desproges gotteron artery originating from the iliolumbar artery are also involved in the blood supply to the spinal conus[ 6 , 23 - 25 ]. At present, the diagnosis of conus medullaris infarction is mainly based on clinical manifestations and MRI findings.…”
Section: Discussionmentioning
confidence: 99%
“…These form a coronary artery ring at the level of the conus medullaris, which then branches from the artery ring into the conus medullaris. In addition, the thick nerve root medullary artery (Adamkiewicz artery) from the intercostal or lumbar artery from T9 to T12 and the desproges gotteron artery originating from the iliolumbar artery are also involved in the blood supply to the spinal conus[ 6 , 23 - 25 ]. At present, the diagnosis of conus medullaris infarction is mainly based on clinical manifestations and MRI findings.…”
Section: Discussionmentioning
confidence: 99%
“…As stated previously, the proposed model is not exclusive to peripherally generated chronic pain as IIS may also offer a physiological rationale for idiopathic visceral and vascular dysfunction. Neurovascular bundles from all spinal segments also innervate vertebral and spinal cord vessels, making them capable of inducing spinal vasospasm by activating SNA ( 130 , 131 ). Vasoconstriction of spinal arteries and veins may contribute to the pathophysiology of common disorders including radiculopathies, myopathies, idiopathic neuropathies, degenerative disc disease and/or degenerative joint disease.…”
Section: Discussionmentioning
confidence: 99%
“…Some neurotransmitters are directly vasoactive, such as adenosine, acetylcholine, catecholamines, and neuropeptides; 37 other neurotransmitters are not vasoactive but stimulate the production of vasodilators, including NO, metabolites of cyclooxygenase-2 (COX-2) and P450 epoxygenases, through downstream enzymatic activation in astrocytes and vascular cells. 33,119 However, it is difficult to discern the independent autoregulation mechanism in the CNS through inhibition or activation in experimental investigations because overlapping effects in the NVU provide redundant or synergistic effects in autoregulation. 20 Moreover, despite their sound theoretical background, inducing the generation of arachidonic acid (AA) from phospholipase A2 (PLA2).…”
Section: Signal Transmission In Autoregulationmentioning
confidence: 99%
“…Neurons can release multiple neurotransmitters from nerve endings via the nervi-vasorum, 51 or hierarchically through astrocytes and pericytes, 32 , 118 to adjust vascular reactivity to control vascular reactivity. 119 Several independent studies have reported that many neurotransmitters are involved in autoregulation ( Figure 3 ). Some neurotransmitters are directly vasoactive, such as adenosine, acetylcholine, catecholamines, and neuropeptides; 37 other neurotransmitters are not vasoactive but stimulate the production of vasodilators, including NO, metabolites of cyclooxygenase-2 (COX-2) and P450 epoxygenases, through downstream enzymatic activation in astrocytes and vascular cells.…”
Section: Signal Transmission In Autoregulationmentioning
confidence: 99%
See 1 more Smart Citation